Nadzór nad lecznictwem uzdrowiskowym ze szczególnym uwzględnieniem czynności kontrolno-nadzorczych nad zakładami lecznictwa uzdrowiskowego - Paulina Jachimowicz-Jankowska (Studia Prawa Publicznego, 2021)
Spa treatment, which constitutes an integral part of health care, is an organized activity consisting in providing health care services in the field of spa treatment or spa rehabilitation carried out in a spa by spa treatment facilities. In order to ensure the proper and efficient operation of this form of treatment in specially adapted facilities that are medical entities, this treatment is subject to professional supervision. Supervision over health resort treatment entails the control and evaluation of health resort treatment carried out in health resort treatment establishments. This issue is regulated primarily in the Act of 28 July 2005 on spa treatment, health resorts and health resort protection areas and in health resort communes, as well as in the Act of 15 April 2011 on medical activity. The study contains an analysis and evaluation of the legal regulations concerning the supervision of spa treatment. It discusses the basic terms related to spa issues and presents some concepts of control and supervision in terms of the doctrine. Spa supervision is characterized by specific regulations and the degree of complexity. This applies to individual issues that allow the reconstruction of the essence of supervision. These are the supervisory authorities, subject of supervision, the supervised entities, criteria and scope of supervision exercised and legal means of supervision. The authorities supervising the health resort treatment include the Minister of Health, the Voivode, the Minister of National Defense and the Minister of the Interior. In this article, in the analysis of the scope of his competences and control and supervisory powers great attention is paid to the Minister of Health as the central body of government administration in the field of matters belonging to the department of health administration managed by him. Due to the specific nature of supervision of this treatment carried out in the voivodeship, the legal position of the chief physician of the health resort, with whose help the voivode exercises this supervision, was analyzed. Since spa treatment is carried out in spa facilities in a health resort, the study contains the problem of separate control procedures carried out in this area, within which special attention is paid to internal, management and ad hoc control.